2014
DOI: 10.1007/s00404-014-3323-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual life impact evaluation of different hormonal contraceptives on the basis of their methods of administration

Abstract: Subdermal contraception is slower than both intravaginal and oral hormonal contraceptives in giving these effects, but is more effective after a cycle of 6 months of usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
2
18
0
1
Order By: Relevance
“…In a comparison between the vaginal ring, an oral CHC containing a third-generation progestin, subdermal contraception, and no hormonal contraception (control group), the three groups using an HC had increased positive indicators of sexual function (sexual interest and fantasies, orgasm number and intensity, and satisfaction) and decreased negative indicators (anxiety and discomfort). The same results were obtained in a comparison between etonogestrel implant and no contraception [2,52]. LNG-IUS have also been positively associated with sexual desire, arousal, orgasm, and overall sexual function compared with no contraception [2,53].…”
Section: Resultssupporting
confidence: 62%
“…In a comparison between the vaginal ring, an oral CHC containing a third-generation progestin, subdermal contraception, and no hormonal contraception (control group), the three groups using an HC had increased positive indicators of sexual function (sexual interest and fantasies, orgasm number and intensity, and satisfaction) and decreased negative indicators (anxiety and discomfort). The same results were obtained in a comparison between etonogestrel implant and no contraception [2,52]. LNG-IUS have also been positively associated with sexual desire, arousal, orgasm, and overall sexual function compared with no contraception [2,53].…”
Section: Resultssupporting
confidence: 62%
“…Moreover, when the implant was compared to other types of contraceptives women who used the subcutaneous implant had higher scores on the McCoy female sexuality questionnaire and higher levels of androstenedione [9, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Influence of hormonal contraceptives on sexual life is not frequently reported. Data published to date are contrasting and refer to the combined short-acting hormonal oral [3, 4] and vaginal contraceptives [5, 6], while studies on the influence of subdermal contraception are few, and not specifically focused on female sexual function [79].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to women using the ring, pill, or no method (control group), after 6 months, implant users reported the most significant improvements in sexual discomfort, anxiousness, personal initiative, and fantasy. All method users reported significantly more sexual pleasure, satisfaction and higher orgasm frequency at 6 months compared to controls (Guida et al, 2014) Women reported that the ring was more likely to interfere with sex compared to the pill and significantly more women reported that their sex partners preferred the pill (Stewart et al, 2007).…”
Section: "Multiplementioning
confidence: 92%